Synthesis and Different Effects of Biotinylated PAMAM G3 Dendrimer Substituted with Nimesulide in Human Normal Fibroblasts and Squamous Carcinoma Cells - Łukasz Uram; Aleksandra Filipowicz-Rachwał; Maria Misiorek; Aleksandra Winiarz; Elżbieta Wałajtys-Rode; Stanisław Wołowiec (Biomolecules, 2019)
Squamous cell carcinoma (SCC) remains a main cause of mortality in patients with neck and head cancers, with poor prognosis and increased prevalence despite of available therapies. Recent studies have identified a role of cyclooxygenases, particularly inducible isoform cyclooxygenase-2 (COX-2) and its metabolite prostaglandin E2 (PGE2) in cancer cell proliferation, and its inhibition become a target for control of cancer development, particularly in the view of recognized additive or synergic action of COX-2 inhibitors with other forms of therapy. Nimesulide (N), the selective COX-2 inhibitor, inhibits growth and proliferation of various types of cancer cells by COX-2 dependent and independent mechanisms. In the presented study, the conjugates of biotinylated third generation poly(amidoamine) dendrimer (PAMAM) with covalently linked 18 (G3B18N) and 31 (G3B31N) nimesulide residues were synthesized and characterized by NMR spectroscopy. Biological properties of conjugates were evaluated, including cytotoxicity, proliferation, and caspase 3/7 activities in relation to COX-2/PGE2 axis signaling in human normal fibroblast (BJ) and squamous cell carcinoma (SCC-15). Both conjugates exerted a selective cytotoxicity against SCC-15 as compared with BJ cells at low 1.25−10 µM concentration range and their action in cancer cells was over 250-fold stronger than nimesulide alone. Conjugates overcome apoptosis resistance and sensitized SCC-15 cells to the apoptotic death independently of COX-2/PGE2 axis. In normal human fibroblasts the same concentrations of G3B31N conjugate were less effective in inhibition of proliferation and induction of apoptosis, as measured by caspase 3/7 activity in a manner depending on increase of PGE2 production by either COX-1/COX-2.